PERILAKU KONSUMSI ISLAMI PARA ALUMNI PONDOK PESANTREN DALAM MENCAPAI KESEJAHTERAAN ISLAM (STUDI KASUS ALUMNI PONDOK PESANTREN ISLAM MIFTACHUS SUNNAH SURABAYA) - Muhammad Ali Ridho; Irham Zaki (Universitas Airlangga, 2019)
Islamic boarding school can train a santri’sIndependence and it can be reflected after a santri becomes an alumni, such from economic welfare. This study aims to determine whether the consumption practice of alumni Islamic boarding school is in line with Islamic welfare or not. The research method used is descriptive qualitative approach by using case studyon alumni of Miftachus Sunnah Islamic boarding school. Data collection is done by in-depth interview, observation, and documentation. The validation technique used by source and technique triangulation. The analysis technique used is Miles- Huberman’s.The five areas of maqashid sharia in dharuriyyat level stand as an indicator of Islamic welfare. The results showed that the consumption practice of alumni of Miftachus Sunnah based on the values (justice, responsibility, and guarantee) and basic principles (efficiency, adequacy, freedom, balance, and solidarity) of Islamic economic behavior in the achievement and guarding of maqashid sharia indicate the suitability. Key words: Consumption behavior, values of Islamic economic, principal of Islamic economic, and maqashid sharia.REFERENCESAlQur’an danHadits.Al-Ghazali, Abu Hamid Muhammad bin Muhammad.tt. Al-Mustashfa. Jilid II. Fakultas Syariah Universitas Islam Madinah Nama pengarang. Tahun. Judul. Nama penerbit atau volume.As-Syatibi, Ibrahim bin Musa. 1997. Al- Muwafaqat. Jilid II. Al-Aqrabiyah: Dar Ibnu Affan. Chaudhry, Muhammad Sharif. Tanpa Tahun. Sistem Ekonomi Islam: Prinsip Dasar.Terjemahan oleh Suherman Rosidi. 2012. Jakarta: Kencana.DITPONTREN. 2016. Analisis dan Interpretasi Data pada Pondok Pesantren, Madrasah Diniyah (Madin), Taman Pendidikan Qur’an (TPQ) Tahun Pelajaran 2014-2015Fadli, Adi. 2012. Pesantren: Sejarah dan Perkembangannya. EL-HIKAM: Jurnal Pendidikan dan Kajian Keislaman, Vol. V Nomor 1, Januari – Juni: 29-42Nata, Abdullah. 2011. Studi Islam Komprehensif. Edisi Pertama, Cet. ke-1. Jakarta : Kencana.Nizar, Samsul (Editor). 2007. SejarahPendidikan Islam. Jakarta: Kencana. Poerwadarminto, WJS. 1999. Kamus UmumBahasa Indonesia. Jakarta: Balai Pustaka.Pusat Pengkajian dan Pengembangan Ekonomi Islam. 2008. Ekonomi Islam. Edisi Kesatu. Jakarta: PT Raja Grafindo Persada——–. 2014. Ekonomi Islam. Edisi Kesatu. Cet. ke-6. Jakarta: PT Raja Grafindo Persada. Samuelson, Paul dan William D Nor Hans.1993. Ekonomi. Jilid I. Jakarta:Airlangga.Sanusi, Uci. 2012. Pendidikan Kemandirian Di Pondok Pesantren (Studi Mengenai Realitas Kemandirian Santri di Pondok al-Istiqlal Cianjur dan Pondok Pesantren Bahrul Ulum Tasikmalaya). Jurnal Pendidikan Agama Islam- Ta’lim, Vol. 10 No. 2: 123- 139Sugiyono. 2012. Metode Penelitian Kualitatif dan Kuantitatif R&D. Bandung: AlfabetaYin, Robert K. 2002. Studi kasus: Desain dan Metode, Terjemahan. Jakarta: PT. Raja Grafindo Persada.————-. 2009. Studi kasus: Desain dan Metode, Terjemahan. Jakarta: PT. Raja Grafindo Persada.Zuhriy, M. Syaifuddien. 2011. Budaya Pesantren dan Pendidikan Karakter pada Pondok Pesantren Salaf. Walisongo, Vol. 19, No. 2, November:287-310